Evaluating joint operation rules for connecting tunnels between two multipurpose dams - Ji-Woo Jeong; Young-Oh Kim; Seung Beom Seo (Hydrology Research, 2020)
This study aims to provide a practically efficient approach for determining the most efficient joint operation rule for two reservoirs connected by a waterway tunnel. For this purpose, the connecting tunnel's effect was assessed and three heuristic joint operation rules accounting for the connecting tunnel were evaluated. A standard operation policy with the connecting tunnel led to positive effects on the water resource system of the target basin with regard to a reliable water supply. The connecting tunnel provides an additional water supply of 12.4 million m3/year to the basin, and the reliability of the two reservoirs increased. Among the three rules, the equivalent reservoir (ER) rule led to the most positive effect on water supply. We found that the ER rule could maximize the positive effects of the connecting tunnel by maintaining the effective water storage rates of the two reservoirs. Moreover, the effects of hydrologic uncertainty on the joint operation rules were discussed using the synthetically generated multiple streamflow traces.